Structure and Properties of Vacuum-arc Coatings of Chromium and Its Nitrides Obtained under the Action of Constant and Pulse High-voltage Bias Potential - Sobol, O. V.; Postelnyk, A. A.; Mygushchenko, R. P.; Al-Qawabeha, Ubeidulla F.; Tabaza, Taha A.; Al-Qawabah, Safwan M.; Gorban, V. F.; Stolbovoy, V. A. (Sumy State University, 2017)
To reveal the regularities of structural engineering of vacuum-arc coatings based on chromium and its nitrides, the influence of the main physicotechnological factors (the pressure of the nitrogen atmosphere and the bias potential) in the formation of coatings was studied. It was discovered that during the deposition of chromium coatings the formation of the texture axis [100], as well as the macrodeformation of compression is happening. The supply of a high-voltage negative pulse potential to the substrate increases the mobility of the deposited atoms and leads to relaxation of the compression deformation. As the pressure increases from Torr, the phase composition of the coatings changes: Cr (JCPDS 06-0694) → Cr2N(JCPDS 35-0803) → CrN(JCPDS 11-0065). The supply of high-voltage pulses leads to the formation of a texture of crystallites with parallel growth surfaces planes having d ≈ 0.14 nm. The structure obtained by pulsed high-voltage action makes it possible to increase the hardness of the coating to 32 GPa and reduce the friction coefficient to 0.32 in the "chromium nitride-steel" system and to 0.11 in the "chromium nitride-diamond" system. The results obtained are explained from the viewpoint of increasing the mobility of atoms and the formation of cascades of displacements when using an additional high-voltage potential in the pulse form during the deposition of chromium-based coatings.

Для виявлення закономірностей структурної інженерії вакуумно-дугових покриттів на основі хрому та його нітридів досліджено вплив основних фізико-технологічних факторів (тиск азотної атмосфери і потенціал зсуву) при формуванні покриттів. Встановлено, що при осадженні покриттів хрому відбувається формування: осі текстури [100], а також макродеформацій стиснення. Подача високовольтного негативного імпульсного потенціалу на підкладку підвищує рухливість атомів, що осаджуються і призводить до релаксації деформації стиснення. Зі збільшенням тиску фазовий склад покриттів змінюється: Cr (JCPDS 06-0694) → Cr2N (JCPDS 35-0803) → CrN (JCPDS 11-0065). Подача високовольтних імпульсів призводить до формування текстури кристаллитов з паралельними поверхні зростання площинами які мають d ≈ 0.14 нм. Одержана при імпульсному високовольтному впливі структура дозволяє підвищити твердість покриття до 32 ГПа і знизити коефіцієнт тертя до 0.32 в системі «нітрид хрому – сталь» і до 0.11 в системі «нітрид хрому – алмаз». Одержані результати пояснені з позиції підвищення рухливості атомів і утворення каскадів зміщення при використанні в процесі осадження покриттів на основі хрому додаткового високовольтного потенціалу в імпульсної формі.
Структура і властивості вакуумно-дугових покриттів хрому і його нітридів, отриманих в умовах дії постійного і імпульсного високовольтного потенціалів зсуву
Keywords: vacuum arc; pressure; bias potential; pulse potential; phase composition; structure; hardness; friction coefficient; фізичні реакції; твердість; коефіцієнт тертя; структурна інженерія; напруга; імпульси